24-epibrassinolide induces protection against waterlogging and alleviates impacts on the root structures, photosynthetic machinery and biomass in soybean. (1st November 2020) - Pereira, Ynglety Cascaes; Silva, Fernanda Rodrigues da; Silva, Breno Ricardo Serrão da; Cruz, Flávio José Rodrigues; Marques, Douglas José; Lobato, Allan Klynger da Silva
ABSTRACT: Plants exhibit several restrictions under waterlogging conditions, including stomatal limitations, negative impacts on gas exchange, lower nutrient uptake and reduced growth. 24-epibrassinolide (EBR) is a polyhydroxylated steroid, with the advantages to be a natural and biodegradable molecule, presenting beneficial roles in metabolic and physiological processes. The aim of this research is to investigate whether EBR can protect soybean plants against damage caused by waterlogging and evaluate the responses associated with the root and leaf anatomy, photosynthetic machinery and biomass. This study used a completely randomized factorial design with two water conditions (control and waterlogging) and three concentrations of 24-epibrassinolide (0, 5 and 10 nM EBR). This steroid stimulated the activities of enzymes linked to the antioxidant system and resulted in minor damage to the chloroplast membranes. EBR maximized the efficiency of photosystem II and improved the gas exchange, which was explained by the higher density and index of the stomata in addition to the increased chlorophyll content and electron transport rate. In root structures, EBR mitigated the impact of waterlogging on vascular cylinder and metaxilem, suggesting maintenance and functions of these structures in plants stressed.